2022
DOI: 10.3389/fonc.2022.878472
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Baseline Muscle Mass and Myosteatosis on the Development of Early Toxicity During First-Line Chemotherapy in Patients With Initially Metastatic Pancreatic Cancer

Abstract: ObjectivesAlthough chemotherapy is the only treatment option for metastatic pancreatic cancer (PDAC), patients frequently encounter adverse events during chemotherapy leading deterioration of patients’ quality of life and treatment interruption. We evaluated the role of baseline CT-assessed body composition in predicting early toxicity during first cycle of the first-line chemotherapy in patients with metastatic PDAC.MethodsThis retrospective study included 636 patients with initially metastatic PDAC who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A higher SKM mass, often measured using the SKM index, is correlated with improved prognosis in patients with cancers of various origins, including biliary tract, brain, breast, esophageal, gastric, liver, small-cell lung, ovarian, pancreatic, urothelial, and pediatric malignant solid cancers [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. For example, a 2010 meta-analysis demonstrated that lower muscle mass was associated with an all-cause mortality hazard ratio of 1.44 in patients with solid cancers [ 60 ], although the effect is likely at least partially due to better resistance to chemotherapy-induced dysfunction supported by increased SKM mass.…”
Section: Epidemiological and Mechanistic Studiesmentioning
confidence: 99%
“…A higher SKM mass, often measured using the SKM index, is correlated with improved prognosis in patients with cancers of various origins, including biliary tract, brain, breast, esophageal, gastric, liver, small-cell lung, ovarian, pancreatic, urothelial, and pediatric malignant solid cancers [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. For example, a 2010 meta-analysis demonstrated that lower muscle mass was associated with an all-cause mortality hazard ratio of 1.44 in patients with solid cancers [ 60 ], although the effect is likely at least partially due to better resistance to chemotherapy-induced dysfunction supported by increased SKM mass.…”
Section: Epidemiological and Mechanistic Studiesmentioning
confidence: 99%
“…A higher SKM mass, often measured using the SKM index, is correlated with improved prognosis in patients with cancers of various origins, including biliary tract, brain, breast, esophageal, gastric, liver, small-cell lung, ovarian, pancreatic, urothelial, and pediatric malignant solid cancers [26][27][28][29][30][31][32][33]. For example, a 2010 meta-analysis demonstrated that lower muscle mass was associated with an all-cause mortality hazard ratio of 1.44 in patients with solid cancers [34], although the effect is likely at least partially due to better resistance to chemotherapy-induced dysfunction supported by increased SKM mass.…”
Section: Epidemiological and Mechanistic Studiesmentioning
confidence: 99%
“…Cancer cachexia is a multifactorial disorder characterized by the involuntary loss of body weight that results predominantly from loss of skeletal muscle and fat mass. 1 In this situation, skeletal muscle atrophy is recognized as an independent risk factor for the impairment of quality of life 2 and poor survival in cancer patients, 3 because it contributes to reduced chemotherapy treatment tolerance 4 and increased surgical complications. 5 The loss of skeletal muscle mass results, in part, from an imbalance between muscle protein breakdown and synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%